HISTOMORPHOLOGICAL CHANGES IN STOMACH AND LIVER OF NEMACHEILUS EVEZARDI (DAY) ON ACUTE EXPOSURE OF AQUEOUS EXTRACT OF LEAVES OF CESTRUM NOCTURNUM (LINN.) - PATOLE, S.S.; MAHAJΑΝ, R.T. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2006)
Investigations were undertaken to evaluate the toxic effect of aqueous extract of the leaves of Cestrum nocturnum (Linn.) to a freshwater fish Nemacheilus everardi (Day). The results reveal that the fish is very sensitive to the steroid saponins and alkaloids present in the leaves of this ornamental plant. Present findings are correlated with the changes noted in the organism after exposure to digitonin, a potent ichthyotoxin of plant origin. Deleterious effect was seen as histomorphological features of stomach showed ruptured epithelial cells, vacuolization in lamina propria. reduced length of mucosa and shrinkage due to crumpled mucosal folds as compared with effects observed in control group of animals. This extract at the same dose and duration of exposure causes changes in histomorphology of liver cells, as revealed from microscopic examination of tissues. Concomitantly, deviation from normal structure of liver was also recorded, this included ruptured cell membrane. hypertrophy. Vacuolization and degeneration. Alterations in histological features of mucosal layers of Stomach and architecture of hepatocytes are almost parallel with digitonin toxicated organisms. These results conclusively established deleterious effects of the toxic principles i.e. Steroids. Saponins and alkaloids of C. nocturnum on fish, which cause toxicity and ultimate death of animals.